Integrated intelligent computing paradigm for the dynamics of micropolar fluid flow with heat transfer in a permeable walled channel - Mehmood, Ammara; Afsar, Khan; Zameer, Aneela; Awan, Saeed Ehsan; Raja, Muhammad Asif Zahoor (Applied soft computing, 2019)
In this work, a novel application of bio-inspired computational heuristic paradigm is presented for micropolar fluid flow and heat transfer system in a channel with permeable walls by modeling competency of neural networks, global search of genetic algorithms, and rapid local convergence of sequential quadratic programming. Approximation theory in the mean squared error sense is exploited for the formulation of an objective function to solve the governing nonlinear fluidics system. The designed scheme is employed to study the dynamics of the model in terms of stream function, microrotation, concentration, and temperature profiles for prominent factors based on Reynolds number, Peclet number for diffusion of heat and mass, coupling, spin-gradient viscosity, micro inertia density parameters. The consistency and robustness of the solver are validated through statistical performance indices based on comparison with state of art Adams numerical method for accuracy and complexity measures. [Display omitted] •A novel integrated heuristic is designed for a system of micropolar fluidic model.•Consistent accuracy is achieved in concurrence with the Adams numerical method.•Validation of the accuracy and convergence is certified through results of statistics.•Applicability and smooth implementation are other creditable attractions of the scheme.